KARAKTERISTIK TINGKAT ASUPAN ZAT BESI DAN POLA MENSTRUASI TERHADAP KEJADIAN ANEMIA PADA REMAJA PUTRI: Literature Review - Miranti Nisrina Nugrahanti (2020)
In 2015, the worldwide prevalence of anemia stated that people in the world who experienced an incidence of anemia had a prevalence of 40 - 88%. Whereas in Southeast Asia, accorded to the WHO Regional Office of the South East Asia Region Organization (ROSEARO) the prevalence of adolescent girls suffering from anemia is 25-40% with mild to severe anemia. This literature study was conducted to elaborate evidence-based information in the field of nursing regarding the characteristics of iron (Fe) intake levels and menstrual patterns with the incidence of anemia in adolescent girls. This literature study analyzed 30 international journals according to topic by assessing the quality of these journals. The conclusion of this literature study is that most of the journals get research results that have a relationship between the level of iron intake and menstrual patterns with the incidence of anemia and the results of the journal quality assessment obtained good grades. The suggestion of this research is the government makes a policy in giving iron supplements to young women to prevent and overcome anemia.